ESTGenes: Alternative Splicing From ESTs in Ensembl - Eyras, Eduardo; Caccamo, Mario; Curwen, Val; Clamp, Michele (Genome Research, 2004)
We describe a novel algorithm for deriving the minimal set of nonredundant transcripts compatible with the splicing structure of a set of ESTs mapped on a genome. Sets of ESTs with compatible splicing are represented by a special type of graph. We describe the algorithms for building the graphs and for deriving the minimal set of transcripts from the graphs that are compatible with the evidence. These algorithms are part of the Ensembl automatic gene annotation system, and its results, using ESTs, are provided at www.ensembl.org as ESTgenes for the mosquito, Caenorhabditis briggsae, C. elegans, zebrafish, human, mouse, and rat genomes. Here we also report on the results of this method applied to the human and mouse genomes.